2012
DOI: 10.1016/j.ijge.2012.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Bloodstream Infections in the Elderly: Effects of Nursing Homes on Antimicrobial-Resistant Bacteria

Abstract: s u m m a r yObjectives: Emergency room visits by nursing home patients with bloodstream infections (BSIs) are not uncommon and pose challenges to clinicians when selecting appropriate antimicrobial agents. This research aims to discover distinct bacteriology in nursing home patients by focusing particularly on antimicrobial-resistant bacteria. Methods: This retrospective study enrolled patients aged 65 years or older who had documented positive blood culture reports between May 2006 and June 2008. Patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…Even when accounting for age, patients who were admitted from NHs were significantly more likely to have a BSI-POA than patients who were admitted from private homes or other hospitals. Consistent with our findings, other investigators examined BSI among NH and non-NH residents and established that NH exposure was a risk factor for BSI-POA caused by gram-positive and gram-negative organisms (Huang et al, 2012) and another study reported that residence in a long-term care facility was associated with gram-negative BSI-POA (Pop-Vicas et al, 2009). Limitations of these studies included the fact that patients were from a single hospital.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Even when accounting for age, patients who were admitted from NHs were significantly more likely to have a BSI-POA than patients who were admitted from private homes or other hospitals. Consistent with our findings, other investigators examined BSI among NH and non-NH residents and established that NH exposure was a risk factor for BSI-POA caused by gram-positive and gram-negative organisms (Huang et al, 2012) and another study reported that residence in a long-term care facility was associated with gram-negative BSI-POA (Pop-Vicas et al, 2009). Limitations of these studies included the fact that patients were from a single hospital.…”
Section: Discussionsupporting
confidence: 90%
“…other hospital, nursing home [NH], private home), an important factor that can inform interventions. Further, many studies on BSI-POA have been limited to specific organisms (Courjon et al, 2015; Wang et al, 2015), single institutions (Akoua-Koffi et al, 2015; Artero et al, 2010), elderly (Huang et al, 2012) or intensive care units (Artero et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The findings of this study 7 were consistent with studies in the 2005 review 1 and will not be discussed further. The literature review identified 6 studies published since 2005 that met the inclusion criteria [8][9][10][11][12][13] : 2 studies evaluated exclusively NHABSI 8,9 and 4 studies compared NHABSI to community-or hospital-associated BSI. [10][11][12][13] Studies that evaluated exclusively NHABSI Table 1 summarizes the characteristics and findings of the 2 studies in which only NHABSI was evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…The literature review identified 6 studies published since 2005 that met the inclusion criteria [8][9][10][11][12][13] : 2 studies evaluated exclusively NHABSI 8,9 and 4 studies compared NHABSI to community-or hospital-associated BSI. [10][11][12][13] Studies that evaluated exclusively NHABSI Table 1 summarizes the characteristics and findings of the 2 studies in which only NHABSI was evaluated. The study by Almog et al 8 was a letter to the editor and was included in this review because it evaluated a large number of cases of NHABSI (N = 177) and provided information on antibiotic resistance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation